Aligning Technology, Policy and Culture to Enhance Nuclear Security: A Comparative Analysis of Nigeria and the U.S. - Stephen Olumuyiwa Ariyo Dahunsi; John D. Auxier II; Joseph Ruric Stainback IV; Howard Lewis Hall (International Journal of Nuclear Security, 2017)
Around the world, current energy and climate change concerns have led to more nations adopting nuclear technology as an option for electricity generation. However, one of the challenges to the peaceful application of this technology is the possibility that it will be misused, or that terrorists with global reach may acquire nuclear materials. Nigeria is one country that has embraced the technology to solve its energy challenges, but the country is now faced with an upsurge in terrorism and uprisings staged by various ethnic groups. In addition, corruption is continually becoming a hindrance to national development. These challenges are critical factors to be considered when vetting and recruiting reliable personnel for peaceful nuclear-related applications. It is important to understand how these human elements and other factors can impact global threats or undermine both Nigeria’s national security as well as international security. Knowledge of these matters will help Nigerian bureaucrats anticipate and correct deficiencies that might evolve from current procedures being degraded by these emerging threats and will prevent any catastrophe that any of the highlighted challenges could bring about. Being aware of these challenges and introducing appropriate policy will provide critical guidance to Nigeria and other emerging nuclear countries in a way that could lead to significant long-term improvements in management, procedures, and overall security of the facilities and materials. The challenge is to establish a Human Reliability Program (HRP) in order to detect and prevent aberrant behavior, thus effecting the safe, secure, and unhindered application of nuclear technology in Nigeria. In addition, this research suggests a strategy for conducting a national threat assessment and evaluation as a first step that precedes the development of an HRP; such a strategy must consider the range of threats present across the country.
Keywords: nuclear security culture; social and cultural factors; ethnicity; heritage; best practice